Epidemiology, utilisation of healthcare resources and outcome of invasive fungal diseases following paediatric allogeneic haematopoietic stem cell transplantation. Issue 2 (24th November 2019) - Linke, Christina; Ehlert, Karoline; Ahlmann, Martina; Fröhlich, Birgit; Mohring, Daniela; Burkhardt, Birgit; Rössig, Claudia; Groll, Andreas H.
Summary: Background: Epidemiology and management practices of invasive fungal diseases (IFD) after allogeneic haematopoietic stem cell transplantation (HSCT) are a subject of constant change. We investigated the contemporary incidence, diagnostics, antifungal management and outcome at a major paediatric transplant centre in Germany. Methods: The single‐centre retrospective observational study included all paediatric allogeneic HSCT patients (pts) transplanted between 2005 and 2015. Patient‐related data were assessed up to 365 days post‐transplant. The primary endpoint was the incidence of possible, probable and proven IFDs. Secondary endpoints included diagnostics and antifungal treatment; analysis of risk factors; and overall survival with the last follow‐up in January 2017. Results: A total of 221 first (196), second (21) or third (4) procedures were performed in 200 pts (median age: 9 years, range, 0.5‐22) for leukaemia/lymphoma (149) and non‐malignant disorders (72). Prophylaxis was administered in 208 HSCT procedures (94%; fluconazole, 116, mould‐active agents, 92). At least one computed tomography scan of the chest was performed in 146, and at least one galactomannan antigen assay in 60 procedures. There were 15 cases of proven (candidemia, 4; aspergillosis, 4) or probable (aspergillosis, 7) IFDs, accounting for an incidence rate of 6.8%. Overall mortality at last follow‐up was 30%; the occurrence of proven/probable IFDs was associated with a reduced survival probability ( P  < .001). Conclusion: Morbidity and mortality from IFDs at our institution were consistent with data reported from other centres. Utilisation of healthcare resources for prevention, diagnosis and management of IFDs was considerable.